Political economy of state interventions in the Bangladesh food-grain sector - Islam, Nurul (International Food Policy Research Institute, 2014)
This paper illustrates how the evolution of input/output policies in the food-grain sector in Bangladesh have been the result of interaction between various interest groups such as agricultural/rural and industrial/urban groups. The interaction between the diverse viewpoints and responsibilities of the various policymaking institutions engaged in making and implementing foodgrain policies have also affected the decisions of the government. In many instances, the donors engaged in financing development projects/programs in the relevant sectors/projects exercised varying degrees of influence on policy decisions. In a few instances, they joined hands with social scientists/economists in the government or in national think tanks who shared similar views.